Quad-Port MIMO Filtenna With High Isolation Employing BPF With High Out-of-Band Rejection - Rania R. Elsharkawy; Anwer S. Abd El-Hameed; Shaza M. El-Nady (IEEE Access, 2022)
A quad-port multiple-input multiple-output (MIMO) filtenna with compact dimensions of $50×50$ mm2 is arranged. In this MIMO filtenna, each element is placed orthogonal to its adjacent one to enhance the isolation. The MIMO element is configured based on the novel COVID-19 virus shape with a co-planar waveguide (CPW) feeding structure and dimensions of $17×22$ mm2. The element bandwidth ranges from 3.3 GHz to more than 60 GHz. Three frequency notches are designed at 3.5 GHz for WiMAX, 5.5 GHz for WLAN, and 8.5 GHz for X-band applications. A bandpass filter (BPF) with high out-of-band rejection is used as a decoupling structure (DS) to improve the isolation to more than 30 dB across most of the bandwidth. The BPF is designed based on LC lumped elements, and then implemented using planar strip lines. The proposed MIMO filtenna system provides an impedance bandwidth of 2.4–18 GHz, a peak gain of 5 dBi, and an envelope correlation coefficient (ECC) less than 0.00021. In turn, channel capacity loss does not exceed 0.2. The MIMO filtenna is fabricated and measured showing a good agreement between the measured and simulated results.